NUCKS1, a LINC00629-upregulated gene, facilitated osteosarcoma progression and metastasis by elevating asparagine synthesis - Shuo Zheng; Renchen Ji; Hongtao He; Na Li; Chuanchun Han; Jian Han; Xiaodong Li; Lu Zhang; Yuan Wang; Wenzhi Zhao (Cell Death and Disease, 2023)
Abstract Nuclear ubiquitous casein and cyclin-dependent kinase substrate 1 (NUCKS1) has been reported to play an oncogenic role in several cancers. However, the biological functions and regulatory mechanism of NUCKS1 in osteosarcoma have not been fully understood. In this study, we reported that NUCKS1 was significantly increased in osteosarcoma. Depletion of NUCKS1 decreased osteosarcoma cell proliferation and metastasis in vivo and in vitro. Overexpression of NUCKS1 accelerated osteosarcoma cell aggressiveness. Mechanistically, NUCKS1 facilitated asparagine (Asn) synthesis by transcriptionally upregulating asparagine synthetase (ASNS) expression and elevating the levels of Asn in osteosarcoma cells, leading to increased cell growth and metastasis. Inhibition of ASNS or reduction of Asn decreased osteosarcoma cell aggressiveness and impaired the promoting effects of NUCKS1 on tumorigenesis and metastasis. Furthermore, we also found that by acting as a sponge for miR-4768-3p, LINC00629 promoted NUCKS1 expression. Collectively, our findings highlight the role of NUCKS1 in regulating asparagine metabolism and reveal that LINC00629 is an important regulator of NUCKS1 that contributes to NUCKS1 upregulation in osteosarcoma.